2017
DOI: 10.1111/asap.12139
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Health Care Resources, Family Support, and Mental Health Outcomes Among Suicidal Adolescents

Abstract: To inform current public policy regarding suicide prevention, this study examined the longitudinal relationships between four resources (public insurance, primary care services, school-based mental health treatment, and family support) and depression and suicidality in a nationally representative sample of suicidal adolescents (n = 1,355).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…However, a longitudinal study conducted among a large sample of adolescents showed conflicting results. Parental support was predictive of lower levels of depression but was not significantly associated with the outcomes related to suicidal behaviors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a longitudinal study conducted among a large sample of adolescents showed conflicting results. Parental support was predictive of lower levels of depression but was not significantly associated with the outcomes related to suicidal behaviors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study addresses an important gap in the literature, it is also characterized by several notable limitations. First, while consistent with previous measures of parental support using Add Health (LeCloux et al 2017), the items used to construct parental support do not directly reflect attitudes or feelings regarding the child's romantic relationship. Future work should seek to incorporate a distinctive measure of parental support that reflects thoughts and attitudes about of the romantic relationship in which their child is engaged, particularly in the context of an interracial relationship.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, implications for practice include potential transformations for clinical and mental health care such as increased intersectional representation among providers and culturally informed and relevant treatment and prevention strategies. In addition, integrating family support into screening and treatment referral processes (LeCloux et al, 2017) and counseling families to improve parent-child interactions (Bond et al, 2000;Logan et al, 2011) may be particularly valuable given the moderation finding in this study. Finally, boosting community-level trust, relationships, and sense of common good can supplement the effects of family support on suicidality among youth (Maimon et al, 2010), suggesting that the interactions between ecological levels are also worth exploring in future research.…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%